Singing bones : ancestral creativity and collaboration - Curkpatrick, Samuel (Indigenous music of Australia., 2020)
This book documents cross-cultural collaboration between manikay singers from south-east Arnhem Land and the Australian Art Orchestra. The interwoven voices of the project are explored as an example of creative intercultural collaboration and a continuation of the manikay tradition.